One-pot laser-assisted synthesis of porous carbon with embedded magnetic cobalt nanoparticles1. Issue 22 (14th June 2015) - Ghimbeu, Camélia Matei; Sopronyi, Mihai; Sima, Felix; Delmotte, Luc; Vaulot, Cyril; Zlotea, Claudia; Paul-Boncour, Valérie; Le Meins, Jean-Marc
<x xml:space="preserve">Abstract</x> A green one-pot laser synthetic approach for ordered carbon with embedded cobalt nanoparticles having size dependent magnetic properties is reported.